AKULTURASI BUDAYA DALAM PERGAULAN SOSIAL MAHASISWA LOKAL DAN PENDATANG - Niken Utami; Denny Soetrisnaadisendjaja; Agung Fauzi (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2022)
Cultural acculturation is the process of meeting several cultures where the culture will be accepted and processed without causing the loss of the culture itself. Cultural acculturation can occur between students in campus where in fact students come not only from the environment around the campus but also from overseas or immigrants. They always come from different backgrounds, so they have different cultures. This study aims to describe the process of cultural acculturation in the social interactions of local and immigrant students, the forms of cultural acculturation in the social interactions of local and immigrant students, and the inhibiting factors of cultural acculturation in the social interactions of local and immigrant students in the Sociological Education study program at Sultan Ageng Tirtayasa University. The results of study were analyzed based on George Herbert Mead's theory of Symbolic Interactionism. This study used a qualitative method with a case study approach. Data collection technique employed was interview with informant constituting the students of Sociology Education at Sultan Ageng Tirtayasa University. The data analysis technique used was Miles and Huberman’s data analysis technique, involving data reduction; data presentation; and conclusion drawing. The results of study revealed that the acculturation process in local students and immigrants occurred during learning process, student organization, and socialization with residents around boarding house. The forms of cultural acculturation occurring were related to language, culture, and habit. Local students and newcomers in the Sociology Education study program are still able to blend without removing the cultural elements they bring, despite their differences and experience with few obstacles in their implementation including different language and regional origin, as well as obstacles to face-to-face learning restrictions during the pandemic.